CIVILIZATION AND UNIVERSAL VALUES - Dekkar Mohammed Amine,; Bendouba Charif Dine, (International Journal of Innovative Technologies in Social Science, 2025)
Morality is no longer a single, unified concept. Instead, it has evolved into a diverse set of ethics that are influenced by various cognitive domains. These dimensions collectively aim to establish a universal moral framework in contemporary civilization. This shift is particularly important given the moral crises of the past century, as well as the challenges faced at the beginning of this one. The crises stemming from the two World Wars, independence movements, and advancements in technology, medicine, and biology have all contributed to the resurgence of the moral question in its original foundational context. In addition, the ongoing events in Palestinian territories further highlight the relevance of revisiting ethical discussions.Thus, there is a pressing need for the human mind to reconstruct a new understanding of ethics that aligns with these urgent and rapid changes in society. Today's challenge lies in determining how ethics can move beyond traditional, classical frameworks. It is crucial to rethink and revitalize these perceptions in a way that fosters a more humane and self-aware practice. The real test, then, is how ethics can adapt to a dynamic and unpredictable civilization, maintaining its effectiveness and tangible impact amidst these shifts.